Martef Hashoah Museum: Jerusalem’s Presence From the Past - Mayer, Gabriel (Advances in Social Sciences Research Journal, 2018)
Martef Hashoah Museum was founded in 1948 and it was the very first Holocaust museum in Israel. The words translate literally into the “Holocaust Cellar” and some have commonly referred to it as the Chamber of the Holocaust. The primary objective during the founding years was to commemorate and sanctify the martyrs who perished in the Holocaust. In Judaism, martyrdom is called Kiddush Hashem, a meaning that defines “the sanctification of G_d’s name.“ This article’s purpose is to elucidate the narrative as regards the foundational ideology as well as the earliest efforts of the state [Israel] to incorporate commemoration with a distinctly spiritual tome that would be in keeping with the depth of sadness and loss following the Shoah. What happened in the interim years, from then until now has lacked some clearly defined terms and adjustments to account for what it is today and what it was in the beginning.